Impact of seasonal changes on groundwater quality for irrigation purposes in Al-Sharqat, Iraq: A GIS and IWQI approach - Ahmed, Ali, Ali; Mohammed M, Numaan; Nizar N, Ismail (Edelweiss Applied Science and Technology, 2024)
This study aims to develop an Irrigation Water Quality Index (IWQI) and Geographic Information Systems (GIS) to evaluate the groundwater quality of several wells in the Al-Sharqat district, Iraq, for irrigation purposes. The results of IWQI in the summer season showed that 8% of studied wells were categorized as a low-restriction range, while the other wells were within the range of moderate restriction. On the other hand, 75% of the IWQ index in the winter season was in the moderate restriction range, whereas 25% of others were classified as a high restriction. The GIS maps illustrated that the groundwater quality of wells along the Tigris River was suitable for irrigation. Whereas the others located far from the river are almost unsuitable because they have high salinity concentrations. Generally, the groundwater quality in the study area improved during the summer because of the increase in the Tigris River's water level, leading to the dilution of the aquafers.